Membrane Rearrangements in the Maturation of Circulating Human Reticulocytes - Minetti, Giampaolo; Bernecker, Claudia; Dorn, Isabel; Achilli, Cesare; Bernuzzi, Stefano; Perotti, Cesare; Ciana, Annarita (Frontiers in Physiology, 2020)
Red blood cells (RBCs) begin their circulatory life as reticulocytes (Retics) after their egress from the bone marrow where, as R1 Retics, they undergo significant rearrangements in their membrane and intracellular components, via autophagic, proteolytic and vesicle-based mechanisms. Circulating, R2 Retics must complete this maturational process, which involves additional loss of significant amounts of membrane and selected membrane proteins. Little is known about the mechanism(s) at the basis of this terminal differentiation in the circulation, which culminates with the production of a stable biconcave discocyte. The membrane of R1 Retics undergoes a selective remodelling through the release of exosomes that are enriched in transferrin receptor and membrane raft proteins and lipids, but are devoid of Band 3, glycophorin A and membrane skeletal proteins. We wondered whether a similar selective remodelling occurred also in the maturation of R2 Retics. Peripheral blood R2 Retics, isolated by an immunomagnetic method, were compared with mature circulating RBCs from the same donor and their membrane protein and lipid content was analysed. Results show that both Band 3 and spectrin decrease from R2 Retics to RBCs on a “per cell” basis. Looking at membrane proteins that are considered as markers of membrane rafts, flotillin-2 appears to decrease in a disproportionate manner with respect to Band 3. Stomatin also decreases but in a more proportionate manner with respect to Band 3, hinting at a heterogeneous nature of membrane rafts. High resolution lipidomics analysis, on the contrary, revealed that those lipids that are typically representative of the membrane raft phase, sphingomyelin and cholesterol, are enriched in mature RBCs, with respect to Retics, relative to total cell lipids, strongly arguing in favour of the selective retention of at least certain subclasses of membrane rafts in RBCs as they mature from Retics. Our hypothesis that rafts serve as additional anchoring sites for the lipid bilayer to the underlying membrane-skeleton, is corroborated by the present results. It is becoming ever more clear that a proper lipid composition of the reticulocyte is necessary for the production of a normal mature RBC.